Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Pegawai pada Dinas Kesehatan Lombok Timur - Yuniar Affandy; Muhammad Atha’ Iqbal; Masbullah Masbullah; Moh. Juhad (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Human resource development is the process of preparing individuals to take on higher or different responsibilities within an organization, including enhancing intellectual abilities to support efficient task performance. This study aims to determine the extent to which human resource development contributes to improved employee performance at the East Lombok Regency Health Office. The qualitative, descriptive approach involved eight informants, consisting of officials familiar with the implementation of human resource development and staff who had participated in the program. The results indicate that education and training conducted by the East Lombok Regency Health Office have supported improved employee performance, as evidenced by more structured task implementation, public health monitoring surveys, and a decrease in maternal and infant mortality rates. However, in terms of human resource management, there are still shortcomings, with an average of 28 health workers per health facility, both civil servants and non-civil servants, reflecting an imbalance in workforce needs. Furthermore, the implementation of human resource development is supported by leadership commitment, inter-agency collaboration, and budget support from the provincial and central governments. However, it is hampered by limited qualified personnel, frequent policy changes, and the impact of natural disasters.